Long‐term processes affecting restoration and viability of the federal threatened Mead's milkweed (Asclepias meadii) - M. L. Bowles; J. L. McBride; T. J. Bell (Ecosphere, 2015)
Restoration is an important tool for reducing extinction risk of endangered plants. Population viabilities of few plant restorations have been modeled over decadal time periods and linked with genetic and ecological factors that drive restoration processes. We modeled viability of restored populations of Mead's milkweed (Asclepias meadii, Asclepiadaceae), a self‐incompatible perennial herb of eastern tallgrass prairie (TGP), federally listed as threatened in the U.S. From 1994 to 2004, we planted >600 seeds and >800 juvenile plants representing >50 genotypes across seven TGP sites. Propagule type, genotype, seed source, restoration site, precipitation and fire management significantly affected establishment, growth and viability. Plants established from seed had greater mortality and greater genetic and demographic attrition than did juveniles. Seedling growth rates also projected 20–30 yrs to reach flowering stage, and their survivorship provided a metric of site suitability for life cycle completion. Seed germination and juvenile plant size were greater in burned habitat, and juvenile size was also positively correlated with spring precipitation. Seed production required presence of multiple genotypes among flowering plants. Seedlings demonstrated a heterosis effect, with greater germination among seeds derived from inter‐population crosses. However, cumulative growth of planted juveniles as well as population growth (λ) on sub‐optimal habitat conditions tended to be lower for propagules derived from inter‐population crosses, demonstrating outbreeding depression. Although flowering occurred at multiple sites, positive population growth (λ > 1) occurred at only a single site, where increasing fire frequency decreased extinction probability. These results suggest that restoration of viable Mead's milkweed populations is possible in optimal habitat. However, restoration of this species is constrained by high demographic attrition and the long period (20 or more yrs) required to complete its life cycle. Crossing among populations to increase genetic diversity and compatible mating types may result in tradeoffs, with heterosis at early life history stages, but outbreeding depression expressed in older stages. Fire and precipitation are also critical interactive processes driving A. meadii growth and reproduction. They may be most effective when precipitation, a stochastic process, results in greater than average post‐burn rainfall. These constraints may have implications for restoration of other late‐successional plant species.